Successful low-dosage thrombolysis of massive pulmonary embolism in primigravida: A case report - Liao, Jiyang (Medicine (Baltimore), 2018)
RATIONAL: Thrombolysis in primigravida with hemodynamic instability is controversial, especially treatment with low-dosage recombinant tissue plasminogen activator (rtPA), and related studies are extremely rare. Here, we report the case of a 26-year-old primigravida diagnosed with an acute massive pulmonary embolism (PE) that prompted initiation of thrombolysis with low-dose alteplase. PATIENT CONCERNS: The patient was admitted to the Emergency Department with chief complaints of a sudden onset of extremely dyspnea, chest tightness, and confusion over a 6-hour period. She was found to have significant dilation of her right ventricle, moderate pulmonary arterial hypotension, as shown by transthoracic echocardiography, and a typical S1-Q3-T3 pattern, as shown by electrocardiogram (ECG). DIAGNOSIS: Acute massive PE in primigravida. INTERVENTION: The patient underwent intravenous thrombolysis with a half dose of alteplase. OUTCOMES: The fetus lived through this severe event during the mother's stay in the Intensive Care Unit; however, surgical abortion was unexpectedly proposed due to long-term hypoxia and high-risk of relapse and exacerbation and was performed successfully after the agreement of her kin. The patient recovered gradually, and results of her laboratory tests and postsurgical, repeated contrast-enhanced computed tomography had normalized by her 3-month follow-up. LESSONS: Administration of low-dosage alteplase in primigravida with hemodynamic instability is extremely rare and controversial; however, our case suggests that this treatment strategy is relatively safe and feasible. In addition, nonradiometric examination played a major role in the diagnosis of PE in this patient. Because radiation use is contraindicated during pregnancy, these examinations could be the first choice for pregnant patients with suspected PE.